Fenomena Madzhab dan Sekte-sekte di Indonesia: Sebuah Studi Medan Dakwah - Zulkarnain, Fisher (Jurnal Ilmu Dakwah, 2012)
This writing presents the development of mazhab (Islamic school of thought and law) and sects in Indonesia, including discussion the sects that are considered deviating. From social-religious perspective, the development of mazhab and sects in Indonesia is correlated with the development of science and social-religious dynamics of one society. Looking from the perspective of mazhab, Muslim in Indonesia is not only concentrated to Sunni (Syafiâi, Maliki, Hanafi, and Hambali), but also to Syiah that began to reveal in 1990s. Meanwhile, from the development of sects, there is a more dynamic and progressive phenomenon, which frequently goes beyond Muslimâs logic and belief. The revealing sects are actually not the development or extension of conventional sects in Islam, such as Qodiriyah, Jabariyah, and Asyariyah, anymore. The development of the sects has come to theological-pluralist development. However, this writing is to assert that the recent occurrence phenomena of various sects in Indonesia is actually not something new, instead of the extension of mysticism practice.